РЕЛИГИОЗНО-СУФИЙСКИЕ МОТИВЫ АЗЕРБАЙДЖАНСКОЙ НАРОДНОЙ ПОЭЗИИ ХIX ВЕКА (на основе творчества народного творца поэта Мамедгусейна) (Вестник КазНУ. Серия Востоковедения, 2016)
Мақалада ХIX ғасыр азербайжан халық поэзия-сындағы діни-сопылық сарындары туралы жазылған.One of the prominent representatives of Azerbaijanfolk poetry in XIX is Poet Mammadhuseyn. He during allhis creative life lived in Dashkend village of Goycha whichis an eternal land of Azerbaijan which is under Armenianoccupation at this moment and died in this place (1800-1884). The biography of this prominent folk poet isconnected with religious and divine values from thebeginning. He was born in a sacred family which was ahearth of Seid. The poetry of this folk poet is very rich as acontent.
Keywords: поэт Мамедгусейн; АЗЕРБАЙДЖАНСКАЯ НАРОДНАЯ ПОЭЗИЯ